Studying the inhibitory activity of the plant and honey seder towards some pathogenic bacteria - Angham Alwan; Bushra Hamad; Mohsin Issa (College of Education for Pure Sciences, 1999)
Abstract this study was Conducted to estimate the antibacterial activity of the Ziziphus leaves and honey compared with the activity of anumber of antibiotics and other types of honey, the aqueous extract and alcoholic extract were prepared. The results showed that the aqueous extract of the Ziziphus leaves was more effective than the alcoholic extract of the plant on the bacteria studied. It was found that increasing concentration of extract was accompanied by an increase in the effectiveness of inhibitory activity and the concentration 200 mg/cm3 had the best inhibitory effect on all bacteria studied Regarding the impact of Ziziphus honey was found to be effective inhibitory effect than in other species, and 100 mg/cm3 was the most effective. When comparing the effectiveness of the Ziziphus extracts and honey with some antibiotics it was found that the concentration of 200 mg/cm3 of aqueous extract of Ziziphus leaves may have superior the effect on the bacteria studied compared to antibiotics Tetracycline, Rifampin, Doxycycline, Gentamicin. And was comparable in its effect of other antibiotics, Ziziphus honey Display superior to most antibiotics studied depending on the type of bacteria studied.